Cheese and cheese infusions: ecological traps for mosquitoes and spotted wing Drosophila. Issue 12 (19th September 2021) - Peach, Daniel AH; Almond, Max; Ko, Elton; Meraj, Sanam; Gries, Regine; Gries, Gerhard
Abstract: BACKGROUND: Harnessing insect ecology for insect control is an innovative concept that seeks to exploit, among others, insect–microbe ecological interactions for improved control of pest insects. Microbe‐produced cheese odour attracts several dipterans, including host‐seeking mosquitoes, but this phenomenon has not been thoroughly explored for mosquito control. Here we tested the hypothesis that attraction of mosquitoes to cheese odour can be exploited as an ecological trap for mosquito control. RESULTS: In laboratory and/or field experiments, we show that ( i ) each of five cheese varieties tested (Raclette, Pecorino, Brie, Gruyere, Limburger) strongly attracts female Aedes aegypti and Culex pipiens; ( ii ) cheese infusions, or headspace odourant extracts (HOEs) of cheese infusions, significantly affect oviposition choices by mosquitoes, ( iii ) HOEs contain at least 13 odourants; ( iv ) in field settings, cheese infusions more effectively stimulate mosquito oviposition than positive bluegrass infusion controls, and also capture (by drowning) the spotted wing Drosophila, Drosophila suzukii ; and ( v ) home‐made cheese infusions modulate oviposition choices by mosquito females and affect the survivorship of their offspring larvae. CONCLUSION: Our data show that microbial metabolites associated with cheese are attractive to mosquito females seeking hosts and oviposition sites and are likely toxic to mosquito larvae. These microbes and their metabolites could thus be co‐opted for both the attract, and the kill, function of 'attract & kill' mosquito control tactics. Implementation of customizable and non‐conventional nutritional media as microbe‐based ecological traps presents a promising concept which exploits insect ecology for insect control. © 2021 Society of Chemical Industry. Abstract : Microbe‐produced cheese odorants attract mosquitoes and spotted wing Drosophila, and microbe metabolites in cheese infusions kill mosquito larvae. Microbe‐based nutritional media show promise as ecological traps for mosquito control.